PERBEDAAN INTENSITAS NYERI PADA PASIEN INPARTU KALA I FASE AKTIF DENGAN TEKNIK EFFLEURAGE DI PUSKESMAS BENDO KEDIRI - Febrina Dwi Nurcahyanti (Indonesian Journal of Health Development, 2020)
Labor pain is a feeling of discomfort in regards to the presence of uterine contractions, dilation and cervical effacement, decreased presentation, stretch of vagina and perineum that ends in IV childbirth. Labor pains that are not handled in an adequate cause of maternal discomfort and will affect the childbirth process. There are several ways of tackling labor pains with the technique of effleurage. The purpose of research is to know the decrease in pain intensity in patients inpartu Kala active phase with the technique effluerage in the work area of Bendo District Puskesmas Kediri year 2019. Experimental Quasy research with the design of one group Pretest-posttest design. The population in this study is all patients inpartu during the active phase in the work area of Bendo Puskesmas. This research sample is 24 respondents selected accidental sampling. Analysis of data using T-Test dependent and using measuring instrument in the form of a pain scale observation sheet according to Bourbanis. The results showed there was a significant difference in the pain intensity reduction in inpartu patients when I was active phase between the effluerage technique with a p-value of 0.008 < α (0.05). Effluerage technique is effective in reducing pain in inpartu patients during the active phase of 1.42 times. Recommended advice to healthcare professionals in order to help meet the needs of mothers will be comfortable in controlling pain when providing labor relief.